(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The goal of this work is the design of LED lamp with adjustable spectral characteristics. The spectral power distribution (SPD) of the lamp can be adjusted to imitate the SPD of the daylight at noon and at evening. Noon light is “bluish” and stimulates cognitive abilities, work productivity and attention; sunlight at evening doesn’t inhibit melatonin production leading to improved sleep during the night and better health. Special combinations of LEDs with different spectral and power characteristics and proper control of the LEDs’ operation are used to achieve the required spectral characteristics of the lamp. Thermal management investigations are made at various ambient temperatures ranging from 20ºC to 45ºC and different current values through LEDs – up to their maximum values. They allow determining safety operating conditions for LEDs depending on the ambient conditions.